Father Found - Johnson, RM. (Simon & Schuster Inc., 2000)
Is there such a thing as too much dedication? Zale Rowen is no ordinary nine-to-fiver. His job is an all-consuming, round-the-clock obsession, propelling him through the underside of Chicago in search of homeless youths. As the founder of an organization called Father Found, Zale is fiercely devoted to a single mission in life: to track down deadbeat dads and hold them accountable to the children they've walked out on. Though Zale's heart is in the right place, something is very wrong. The more his determination builds, the more he spirals out of control, ruining his most valued relationships, destroying his health, and jeopardizing his life. Now on the brink of undermining the very organization for which he's sacrificed everything, Zale is forced to take a step back and consider his behavior. But just as he finally begins to face the dark, long-repressed secrets motivating him, he is blindsided by a shocking revelation that challenges everything he holds true -- one that will change his life forever...
Keywords: Fiction